Comparison of Neonatal Abstinence Syndrome Treatment with Sublingual Buprenorphine versus Conventional Opioids - Hall, Eric S.; Rice, Ward R.; Folger, Alonzo T.; Wexelblatt, Scott L. (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare duration of opioid treatment and length of stay outcomes for neonatal abstinence syndrome (NAS) using sublingual buprenorphine versus traditional weaning with methadone or morphine.Study Design This retrospective cohort analysis evaluated infants treated for NAS at a single community hospital from July 2013 through June 2017. A standardized weaning protocol was introduced in June 2015, allowing for treatment with sublingual buprenorphine regardless of type of intrauterine opioid exposure. General linear models were used to calculate adjusted mean duration of opioid treatment and length of hospitalization with 95% confidence intervals for infants treated with buprenorphine compared with traditional weaning with either methadone or morphine.Results A total of 360 infants were treated with either buprenorphine (n = 174) or a traditional opioid (n = 186). Infants treated with buprenorphine experienced a 3.0-day reduction in opioid treatment duration of 7.4 (6.3–8.5) versus 10.4 (9.3–11.5) days (p < 0.001) and a 2.8-day reduction in length of stay of 12.4 (11.3–13.6) versus 15.2 (14.1–16.4) days (p < 0.001).Conclusion Our study provides an independent confirmation that among infants experiencing NAS following a wide array of intrauterine opioid exposures, buprenorphine weaning supports a shortened treatment duration compared with conventional weaning agents.
Keywords: buprenorphine; drug testing; infant; methadone; morphine; NAS; opioids; weaning